An innovative hybrid steam-microwave sterilization of palm oil fruits at atmospheric pressure - Tee*, Kah Hock; Girma, T. Chala*; How, H.Cheng (Elsevier, 2020)
Conventional sterilization in palm oil mills utilizes heat to soften the fresh-fruit bunch in a pressurized vessel to detach the mesocarp, kernel and nut from the fruitlet. It also inactivates the generation of lipase enzyme that triggers the formation of Free Fatty Acid (FFA) and breaks the oil-bearing cells for easier oil extraction. However, the utilization of a pressurized-vessel encounters frequent production interruptions due to regular inspections of pressure vessel, which finally reduces production efficiencies. To improve the efficiency of the sterilization process, the microwave irradiation technology was introduced to efficiently halt the reaction of enzymatic lipolysis leading to FFA production. The present study proposes an innovative atmospheric-pressured hybrid steam-microwave method to perform sterilization of palm oil fruits under a continuous process without a need to use the pressurized vessel. The analysis is focused at establishing the feasibility of the adoption of hybrid sterilization process for future implementation in palm oil industry. Physical properties of fruit were determined. It was observed that the microwave process heated up the kernel efficiently with a shorter duration. The post steaming process also maintained the moisture content of the mesocarp, which in turn yields better oil quality. The temperature under the hybrid system increased by 17.5% for the mesocarp and 25.1% for the kernel. The process exhibited shorter heating duration and could be useful for industrial applications.